Ego-documents and their role in scientific studies - Szulakiewicz, Władysława (Przegląd Badań Edukacyjnych (Educational Studies Review), 2013)
The article tries to demonstrate the significant role of ego-documents in scientific studies. The article presents their characteristics and indicates their biographical nature. In addition to that, it also describes reasons behind the distorting of historical truth, contained in memoirs. Thanks to the examples presenting the use of various memoir-based sources in scientific studies, it was possible to emphasize their significance in reconstructing the history of pedagogy, education and learning.